LOMBA MEMBACA AYAT ALKITAB DALAM BAHASA INGGRIS UNTUK MENINGKATKAN PELAFALAN DAN KOSAKATA BAGI ANAK SEKOLAH MINGGU - Gracia Otta (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2023)
This community service aims to increase interest and skills in reading aloud in English as well as interpretation skills and English vocabulary when reading Bible verses for Sunday School children who are also students in elementary and secondary schools. The method used in this service was by paying attention to the voice, intonation, and stress appropriately followed by understanding the meaning of the reading by the reader through a Bible reading competition in English. The results of this service showed that the Sunday School children were eagerly and enthusiastically able to take part in the competition to read aloud Bible verses, although gradually they need to be trained again how to read aloud with the right voice, intonation, stress, and pronunciation of English words.